Effect of Soyghurt Fortification with Syzygium myrtifolium Walp. Leaves Extract on Antioxidant Activity - Susanti, Susanti; Rizkuloh, Lina Rahmawati; Mardianingrum, Richa (Integrated Research and Testing Laboratory (LPPT) Universitas Gadjah Mada, 2025)
Soyghurt contains antioxidant compounds such as isoflavones which is derived from soybeans as main ingredient for making soyghurt. To increase antioxidant activity, it is necessary to add other antioxidant compounds such as anthocyanins which is found in Syzygium myrtifolium Walp. which also acts as a red pigment. The aim of this study was to determine the effect of adding Syzygium myrtifolium leaf extract to the antioxidant activity of soyghurt. It began with the making of soy milk then fermented with Lactobacillus bulgaricus into soyghurt. Plants were extracted by maceration in ethanol and made a dry extract. The addition of dried extract to soyghurt was carried out in 3 concentrations, 1%, 3% and 5%. The results of antioxidant activity assay using the free radical DPPH scavenging method showed that there was a decrease in the IC50 in soyghurt fortified with extract compared to soyghurt without extract. The higher concentration of extract, the smaller IC50 value. Soyghurt with 5% extract had the smallest IC50 (694.14 g/mL) while the IC50 of soyghurt without extract was 2823.17 g/mL. The conclusion is that fortification of Syzygium myrtifolium leaf extract has an effect on the antioxidant activity of soyghurt.